Blended Learning Perspectives and Practices at Higher Education Department Colleges in Faisalabad - Muhammad Qaisar Bilal; Dr. Wajiha Kanwal; Arsahad Mehmood Qamar (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study presents Blended Learning (BL) perspectives and practices at Punjab Higher Education Department colleges in the district of Faisalabad, Pakistan. The study was carried out under a descriptive survey design. A sample of 105 college teachers, teaching BS-level subjects in Graduate colleges in the Faisalabad district was selected for this study. A 5-point Likert scale questionnaire was used to obtain responses from the respondents. Descriptive data analysis methods were used to evaluate quantitative data. College teachers expressed a positive attitude towards blended learning. They recognized the value of BL for improved learning possibilities, time flexibility, interest, and student motivation. They also practice blended learning in their institution. But this practice is not common and consistently throughout the institutions. There is no formal spot and mechanism of BL practices in higher education department colleges.